2008
DOI: 10.1016/j.renene.2008.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Bio-hydrogen production from food waste and sewage sludge in the presence of aged refuse excavated from refuse landfill

Abstract: a b s t r a c tIn this work, the aged refuse (AR) excavated from a typical refuse landfill with over 10 years of placement was used for the enhancement of bio-hydrogen production from food wastes. Firstly, the food wastes taken from a university dining hall were inoculated with sewage sludge (SL) pre-treated by 15 min heating at 80 1C. It was found that below 0.4% of hydrogen concentration could be detected in the biogas produced due to its severe acidification properties. However, the addition of AR (50% in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(23 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Table 1 shows perfect exchangeable adsorptive properties for the AR with available specific surface area of 3.376 m 2 g-1. The texture grading of the screened AR shows that the AR media is similar to loamy clay with an average moisture content of 29.5% which is close to values obtained from similar studies [20,30]. This percentage of moisture will also provide the required oxygen for aerobic microorganisms to grow and when there is lack of oxygen the anaerobic microorganisms take place.…”
Section: Resultssupporting
confidence: 80%
“…Table 1 shows perfect exchangeable adsorptive properties for the AR with available specific surface area of 3.376 m 2 g-1. The texture grading of the screened AR shows that the AR media is similar to loamy clay with an average moisture content of 29.5% which is close to values obtained from similar studies [20,30]. This percentage of moisture will also provide the required oxygen for aerobic microorganisms to grow and when there is lack of oxygen the anaerobic microorganisms take place.…”
Section: Resultssupporting
confidence: 80%
“…However, Ming et al . found that the addition of aged refuse excavated from a typical refuse landfill to food waste + sewage sludge considerably increased the hydrogen content in the biogas composition from 0.4 to 26.6%. The pH value was dropped from 6.7 ± 0.23 (feedstock) to 4.72 ± 0.4 (digestate) for all experiments (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…H 2 content remained unaffected at a value of 68-72% during the whole experimental period, which is substantially higher than those reported by Tawfik et al [45] for co-digestion of kitchen; wastewater with OFMSW. However, Ming et al [48] found that the addition of aged refuse excavated from a typical refuse landfill to food waste + sewage sludge considerably increased the (Figure 7c). The addition of sodium bicarbonate maintained a final pH above 4.72, which is the optimum value for H 2 production process.…”
Section: Effect Of Initial Carbon To Nitrogen (C/n) Ratiomentioning
confidence: 96%
“…Hydrogen is a clean energy source with a high-energy yield (122 kJ/g), producing only water when it burns [1]. Although steam reforming, thermal cracking of natural gas, and electrolysis of water are well-known methods of hydrogen production, they are cost and energy intensive.…”
Section: Introductionmentioning
confidence: 99%